Activation of Pannexin-1 channels causes cell dysfunction and damage in mesangial cells derived from angiotensin II-exposed mice - Lucero, Claudia M.; Navarro, Laura; Barros-Osorio, Cristián; Cáceres-Conejeros, Patricio; Orellana, Juan A.; Gómez, Gonzalo I. (Frontiers in Cell and Developmental Biology, 2024)
Chronic kidney disease (CKD) is a prevalent health concern associated with various pathological conditions, including hypertensive nephropathy. Mesangial cells are crucial in maintaining glomerular function, yet their involvement in CKD pathogenesis remains poorly understood. Recent evidence indicates that overactivation of Pannexin-1 (Panx1) channels could contribute to the pathogenesis and progression of various diseases. Although Panx1 is expressed in the kidney, its contribution to the dysfunction of renal cells during pathological conditions remains to be elucidated. This study aimed to investigate the impact of Panx1 channels on mesangial cell function in the context of hypertensive nephropathy. Using an Ang II-infused mouse model and primary mesangial cell cultures, we demonstrated that in vivo exposure to Ang II sensitizes cultured mesangial cells to show increased alterations when they are subjected to subsequent in vitro exposure to Ang II. Particularly, mesangial cell cultures treated with Ang II showed elevated activity of Panx1 channels and increased release of ATP. The latter was associated with enhanced basal intracellular Ca 2+ ([Ca 2+ ]i) and increased ATPmediated [Ca 2+ ]i responses. These effects were accompanied by increased lipid peroxidation and reduced cell viability. Crucially, all the adverse impacts evoked by Ang II were prevented by the blockade of Panx1 channels, underscoring their critical role in mediating cellular dysfunction in mesangial cells. By elucidating the mechanisms by which Ang II negatively impacts mesangial cell function, this study provides valuable insights into the pathogenesis of renal damage in hypertensive nephropathy.